2015
DOI: 10.1021/acs.energyfuels.5b00430
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Titania Nanoparticles in Cross-linking Hydroxypropyl Guar Used in Hydraulic Fracturing Fluids For Oil Recovery

Abstract: Fluids pumped in hydraulic fracturing operations constitute highly viscous gels achieved via cross-linking of the polysaccharide derivative hydroxypropyl guar (HPG), e.g., with titanium or zirconium complexes. In this study, the mechanism underlying the cross-linking effect was clarified experimentally for the titanium system. It was found that the cross-linking effect is not based on a ligand exchange reaction with the cis-hydroxy functionalities present in HPG but instead relies on TiO2 nanoparticles resulti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 72 publications
(45 citation statements)
references
References 25 publications
1
43
0
1
Order By: Relevance
“…Additionally, in Stage II, Ti precursor (TTiP) was added during the synthesis, and its cations were observed in the case of 20.4 wt.% TiO 2 /SWP700_48 mm and 20.4 wt.% TiO 2 /STARBON-800_48 mm (Table 3 and 4) by the presence of small at. [34,36] Additionally, the FT-IR bands in 700-900 cm À1 pointed out Ti-OÀTi bond in the TiO 2 anatase phase. It is well known that low frequencies ultrasound may induce oxygen vacancies and Ti 3 + which may be responsible for morphological, optical and surface changes in the prepared composite materials and may also help to control the course of sonocrystallization processes.…”
Section: Proposed Plausible Mechanism For the Formation Of Crystallinmentioning
confidence: 98%
See 2 more Smart Citations
“…Additionally, in Stage II, Ti precursor (TTiP) was added during the synthesis, and its cations were observed in the case of 20.4 wt.% TiO 2 /SWP700_48 mm and 20.4 wt.% TiO 2 /STARBON-800_48 mm (Table 3 and 4) by the presence of small at. [34,36] Additionally, the FT-IR bands in 700-900 cm À1 pointed out Ti-OÀTi bond in the TiO 2 anatase phase. It is well known that low frequencies ultrasound may induce oxygen vacancies and Ti 3 + which may be responsible for morphological, optical and surface changes in the prepared composite materials and may also help to control the course of sonocrystallization processes.…”
Section: Proposed Plausible Mechanism For the Formation Of Crystallinmentioning
confidence: 98%
“…% of Ti 4 + and Ti 3 + which surface concentration increase further with the treatment steps. [30][31][32][33][34][35][36] Increase in the intensity of these bands was also attributed to the successful formation of titania nanoparticles on the lignocellulosic carbon surface. In Stage III, water was added during the synthesis, and its presence has been mainly observed in the case of 20.4 wt.% TiO 2 /SWP700_ 48 mm ( Figure 10) and 20.4 wt.% TiO 2 /STARBON-800_48 mm ( Figure 11) by a characteristic broad peak in the 3200-3600 cm À1 region (Figure 12).…”
Section: Proposed Plausible Mechanism For the Formation Of Crystallinmentioning
confidence: 99%
See 1 more Smart Citation
“…High viscosity gels were prepared by cross-linking polysaccharide derivative hydroxypropyl guar (HPG) with titania nanoparticles. [59] Results indicated that the 6 nm titania nanospheres can increase the viscosity of a HPG solution by a factor of 25 due to the formation of hydrogen bonds between OH groups present on the surface of titania and on the galactomannan chain of HPG. Li et al [60] studied the effect of nanoparticles in enhancing CO 2 fracturing in unconventional gas reservoirs.…”
Section: Enhanced/improved Oil Recovery (Eor/ior)mentioning
confidence: 99%
“…For example, silver nanoparticles are used in textiles, fridges or washing machines, due to their antibacterial properties [2]. Titanium dioxide nanoparticles are used in sunscreens in order to achieve a better protection from UV radiation, and in hydraulic fracturing fluids for oil recovery [3]. Since data on toxicity are barely available, their increasing application in cosmetic products, food and their release in the environment might cause severe problems.…”
Section: Introductionmentioning
confidence: 99%